2021
DOI: 10.1088/1757-899x/1180/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of inhomogeneous chamber states in rotary positive displacement vacuum pumps

Abstract: Chamber model simulation is a common approach to simulate rotary positive displacement vacuum pumps. Therefore the pump is abstracted into working chambers and connecting clearances, whereby the clearance leakages can be identified as the major loss mechanism in such machines. The clearance mass flow rates are calculated with respect to the thermodynamic states in the adjacent chambers, which are normally considered to be homogeneous. In this work it is shown, that the chamber state is inhomogeneous for rarefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…Regarding the inhomogeneous model from reference [10] (blue line) the curve is not affected in the high pressure regime, but collapses at low suction pressures in qualitatively good agreement with the measurements. But the new model in the current implementation slightly seems to overrate the effect, as the results indicate a worse suction speed than the measurements.…”
Section: Impact Of the Inhomogeneous Chamber Statessupporting
confidence: 73%
See 3 more Smart Citations
“…Regarding the inhomogeneous model from reference [10] (blue line) the curve is not affected in the high pressure regime, but collapses at low suction pressures in qualitatively good agreement with the measurements. But the new model in the current implementation slightly seems to overrate the effect, as the results indicate a worse suction speed than the measurements.…”
Section: Impact Of the Inhomogeneous Chamber Statessupporting
confidence: 73%
“…In a previous paper it was shown that the chamber states are not homogeneous for rarefied gases but that a pressure gradient occurs in tangential direction of the rotor lobe [10]. This is again highlighted in Figure 2 which shows the chamber model abstraction for a screw spindle vacuum pump (SSVP) with the sketched network of chambers and connecting clearances.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The calculation of clearance flows for rarefied gases including moving boundaries has previously been investigated in references [3], [4] and [5] where a data base for different clearance shapes was created and by [6], [7] and [8] where a 1D model was derived and validated in order to calculate the clearance mass flow rates. The impact of the clearance flow models is shown in reference [9].…”
Section: Introductionmentioning
confidence: 99%